A priority-based weighted clustering algorithm for mobile ad hoc network. (21st February 2019) - Pathak, Sunil; Jain, Sonal
One major problem in clustering is the setback involved in cluster formation, cluster maintenance and in the selection of a suitable cluster head. In this paper we have proposed a priority-based weighted clustering algorithm for MANETs which works on three approaches to reduce cluster head changes and clustering overhead. The first phase helps to dynamically determine the cluster head based on their initial priority of neighbour nodes within cluster. The second and third phase helps in cluster maintenance and selecting the new cluster head automatically without any delay when remaining battery power of old cluster head reaches up to the minimum threshold value or in the absence of cluster head. From the simulation result, it is clear that the proposed algorithm reduces the frequent cluster head changes, communication overheads and also improves the efficiency of transmission in the network. Priority of each mobile node is calculated based on node degree and battery power.